Examination of mechanical properties of 3D printed geopolymer mortar using the Taguchi method - Tanyildizi, Harun; Coskun, Ahmet; Seloglu, Maksut; Durmaz, Taner (Springernature, 2025)
This study examined the strength features of 3D printed fly ash-based geopolymer mortar with silica fume using the Taguchi and ANOVA methods. This study used the Taguchi L18(21 x 32) orthogonal array. Silica fume was used in the mixtures at 0% and 10% of the binder weight. 40 x 40 x 160 mm specimens were manufactured by a 3D printer. After the specimens were produced, they were cured at 80 degrees C for 24, 48, and 72 h. Then, these specimens were kept at 20 +/- 2 degrees C for 3, 7, and 28 days. Lastly, the microstructural features, compressive strength, and flexural strength of the samples were determined. The ANOVA results found that the most affecting parameter for the strength properties of geopolymer mortars was found to be silica fume. Also, the Taguchi method found that optimum values of silica fume, curing time, and curing day for strength properties of geopolymer mortar were 10%, 48 h, and 28 days, respectively.
Keywords: 3D printed geopolymer mortar; Silica fume; Fly ash; Strength properties; Taguchi method; ANOVA method